PENGARUH PERENCANAAN ANGGARAN, SISTEM PENGUKURAN ANGGARAN, DAN IMPLEMENTASI ANGGARAN BERBASIS KINERJA TERHADAP AKUNTABILITAS KINERJA PEMERINTAH KABUPATEN BANYUWANGI - Oktavima Wisdaningrum (Jurnal Akuntansi dan Pajak, 2022)
Good governance in the management of public agencies is the result of the accountability of organizational performance. Performance accountability of government agencies is evidence of the duties of government agencies in order to account for the success or failure of implementing the organization's vision and mission in achieving the goals and objectives that have been set. Accountability is believed to be the main factor that can change unfavorable conditions into better ones, especially in public services. This study aims to see the effect of budget planning, budget measurement systems and performance-based budget implementation on the performance accountability of the Banyuwangi Regency Government, the approach method in this research is to use a quantitative approach methodology using SPSS version 20 data processing tools, and the results of this study found there is a positive influence of budget planning and implementation of performance-based budgeting on the performance accountability of the Banyuwangi Regency Government, while the measurement system variable has no effect on the performance accountability of the Banyuwangi Regency Government. The implications of this research are expected to provide scientific contributions and references for the Banyuwangi Regency Government in budget management to support the performance of the Banyuwangi Regency Government.